PENEGAKKAN PRINSIP JURNALISTIK DALAM PEMBERITAAN TELEVISI DI INDONESIA (Analisis Isi Program Berita Pagi di RCTI, TVone Dan MetroTV) - Indah Suryawati; Ica Wulansari (SEMIOTIKA: Jurnal Komunikasi, 2013)
Broadcasting regulation has an important role in controlling broadcasting program. Todays, Television channels are competing to produce attractive programs. News programs become their priority. Consequently, they are required to cover any news accurately and rapidly. News productions are required to be aligned with Pedoman Perilaku Penyiaran dan Standard Program Siaran (P3-SPS) as regulated by KPI. The research method used content analysis. The research is aimed to identify messages transferred bythe TV programs. The analysis has been associated with visual, narrative and journalistic aspects on news program in RCTI, TVOne and Metro TV.Keywords: Content analysis, News Program, P3-SPS, Televison